APPLICATION OF ETHYLMETHAN SULFONATE MUTATION TO INCREASING THE PRODUCTION OF CUCUMBER (Cucumis sativus L.): APLIKASI MUTASI ETIL METANA SULFONAT UNTUK PENINGKATAN PRODUKSI TANAMAN MENTIMUN (Cucumis sativus L.) - Gulo, Alimomon; Sanniwati Saragih, Wismaroh (LPPM UPMI, 2023)
Ethyl Methanesulfonate (EMS) is a stable and effective chemical mutagen. In this study, cucumber (Cucumis sativus L.) seeds were treated with 1% EMS for 12 hours, 24 hours, and 48 hours to optimize EMS mutagenesis and determine the median lethal dose of EMS (1% EMS and 24 hours). This study aims to determine the dose of EMS for cucumber cultivars and report mutant cucumber fruit, flower, vine, and plant sizes induced by EMS. After being treated with 1% EMS for 24 hours, the seeds were grown in a greenhouse for phenotypic investigation. The results showed phenotypic changes, and individual mutants were isolated into six groups, namely: short fruit mutant, long fruit mutant, small flower mutant, large flower mutant, opposite tendril mutant, and group leaf mutant. The mutation frequency is 18.3%. The two selected representatives, the short fruit mutant and the clustered leaf mutant, showed a segregation ratio of 1:3. This ratio is consistent with the classical Mendelian model which shows that the two types of mutants can be controlled by one recessive gene each. The long fruit phenotype was stably inherited, and no segregation was observed in later generations, indicating that this mutant line is probably homozygous.